Broadband Loop Antenna on Soft Contact Lens for Wireless Ocular Physiological Monitoring - Ssu-Han Ting; Bo-Ming Jeng; Wen-Shan Chen; Jin-Chern Chiou; Ching-Hsing Luo (International Journal of Antennas and Propagation)
This paper presents a novel loop antenna with broadband for wireless ocular physiological monitoring (WOPM). The antenna is fabricated on a thin-film poly-para-xylylene C (parylene C) substrate with a small thickness of 11 μm and dimension of π×6.5×6.5 mm2. With the advantage of small size, the proposed antenna is suitable to apply to the soft contact lens and transmit the signal in microelectromechanical Systems (MEMS). Because the pig's eye and human's eye have similar parameters of conductivity and permittivity, the experimental results are obtained by applying the proposed antenna on the pig's eye and cover from 1.54 to 6 GHz for ISM band (2.4 and 5.8 GHz) applications. The measured antenna radiation patterns, antenna gains, and radiation efficiency will be demonstrated in this paper, which are suitable for application of wireless ocular physiological monitoring.